Targeting Oral Squamous Cell Carcinoma with Combined Polo-Like-Kinase-1 Inhibitors and γ-Radiation Therapy - Subhanwita Sarkar; Ayan Chanda; Rutvij A. Khanolkar; Meghan Lambie; Laurie Ailles; Scott V. Bratman; Aru Narendran; Pinaki Bose (Biomedicines, 2024)
Polo-like-kinase-1 (PLK-1) is a serine/threonine kinase that regulates the cell cycle and acts as an oncogene in multiple cancers, including oral squamous cell carcinoma (OSCC). The loss of PLK-1 can inhibit growth and induce apoptosis, making it an attractive therapeutic target in OSCC. We evaluated the efficacy of PLK-1 inhibitors as novel, targeted therapeutics in OSCC. PLK-1 inhibition using BI6727 (volasertib) was found to affect cell death at low nanomolar concentrations in most tested OSCC cell lines, but not in normal oral keratinocytes. In cell lines resistant to volasertib alone, pre-treatment with radiotherapy followed by volasertib reduced cell viability and induced apoptosis. The combinatorial efficacy of volasertib and radiotherapy was replicated in xenograft mouse models. These findings highlight the potential of adding PLK-1 inhibitors to adjuvant therapy regimens in OSCC.